The Ex‐dividend Day Behaviour of REITs: Tax or Market Microstructure Effects. (June 2016) - John, Kose; Mateti, Ravi S.; Nguyen, Duong; Vasudevan, Gopala
Abstract: We examine the importance of the tax and microstructure theories in explaining the ex‐dividend day behaviour of US REIT stock prices in three tick size regimes − the 1/8 th, 1/16 th, and decimal eras. We present a new theory that shows how the tax and microstructure effects interact to produce the observed ex‐dividend day behaviour. Our theory also shows why in an era of a large tick size, as in the 1/8 th era, the tax effects fail to get detected and the observed ex‐dividend day behaviour could be misinterpreted as resulting solely from the microstructure effects.